Design criteria of X-wave launchers for millimeter-wave applications. Issue 9 (27th May 2019) - Fuscaldo, Walter; Pavone, Santi C.; Comite, Davide; Valerio, Guido; Albani, Matteo; Ettorre, Mauro; Galli, Alessandro
Abstract: Bessel-beam launchers are promising and established technologies for focusing applications at microwaves. Their use in time-domain leads to the definition of a new class of devices, namely, the X -wave launchers. In this work, we discuss the focusing features of such devices with a specific interest at millimeter waves. The spatial resolutions of such systems are described under a rigorous mathematical framework to derive novel operating conditions for designing X -wave launchers. These criteria might be particularly appealing for specific millimeter-wave applications. In particular, it is shown that an electrically large aperture is not strictly required, as it seemed from previous works. However, the use of an electrically small aperture would demand a considerably wideband capability. The various discussions presented here provide useful information for the design of X -wave launchers. This aspect is finally shown with reference to the practical design of two different X -wave launchers.